Murka Allah atas Kebebalan Seksual Manusia dalam Roma 1:18-32 - Viktorahadi, R. F. Bhanu (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
Among the myriad of human behaviours, few may provoke the wrath of God such as that of ‘sexual asininity’ (pathe atimias). An expression literally meaning ‘lust for impurity’ or ‘shameful desire’, this refers to homosexual acts be they feminine or masculine. In his letter to Rome 1:18-32, Paul asserts the gravity of this sin as evoking the ire of God upon their heads, the reasons being not only this sin confronts the natural will of the Creator, but even more so for its inclination in leading human to idolatry. Paul clarifies that homosexuality is not the issue per se, but all acts in whatever form they be, should they violate God’s will are displeasing to God. Paul’s starting point was not that of homosexuality leading up to idolatry. On the contrary, the text quotes Paul as explaining that idolatry is the result of erroneous relationship between human and God mirrored in aberrant sexuality. Human errs due to the bond between human and God is not firm. The logical consequence of God’s wrath is punishment. In other words, human’s transgression brings the wrath of God. God’s wrath is not part of the judgment, but a logical consequence streaming from the ill-relationship between the Creator and the creation. Punishment befalls the humankind because of the deviation of the creation’s nature.